(untitled) (Docentes 2.0 Journal, 2023)
In recent years, the techno-pedagogical design has been strengthened as a support tool in the teaching-learning process at different academic levels; in the same way, it is known, promoted, and accepted by some educational institutions worldwide. The purpose of this essay was to emphasize the importance of didactic programming in classrooms supported by technology. The study was framed under the inductive method, in the humanist paradigm, with a qualitative approach of an interpretative type and topical narrative design. Given that, it is imperative to build enterprising, interactive, and collaborative classrooms which approve the reciprocal action of the student in his most active role with the activities, as well as the modification of the traditional role of the educator as an advisor. The work was constituted in two blocks of reflective analysis that arise from the combination of pedagogical knowledge of the content and active didactic methodologies such as cooperative learning, demonstration method, and gamification. To conclude, didactic programming has evolved due to the advancement of technology. However, at present, technology-supported learning and teaching are often carried out without explicit reference to students and teachers since the focus is on technology. Therefore, technology adoption through the current didactic programming has shown low expectations since most teachers have not received equipment or sufficient technological training to carry out a techno-pedagogical design.